INTESTINAL DUPLICATION CYST PRESENTING AS VOLVULUS: A Rare Case Report - Praveen, Chanumolu; Hota, Prasan Kumar; Kumar, Ch.V. Pavan; Babu, K. Maruthi (BALI MEDICAL JOURNAL, 2014)
Intestinal duplication cyst is a rare congenital anomaly occurring anywhere along the alimentary tract, from mouth to anus. They can present with numerous complications like perforation, bleeding or intestinal obstruction. We report a rare case of intestinal duplication cyst of ileum with acute intestinal obstruction due to volvulus with review of literature.